Tuberculosis tenosynovitis of the extensor tendons of the wrist - Mrabet, Dalila (BMJ Publishing Group, 2011)
Mycobacterial tuberculous tenosynovitis of the extensor tendon sheath is an extremely rare manifestation of extrapulmonary tuberculosis. The diagnosis may be easily delayed because of its non-specific clinical signs. We report a new case of tuberculous tenosynovitis of the extensor without concomitant pulmonary tuberculosis or documented immunodeficiency.